Glioma Mimicking Infarct - Ikhwanul Hakim Nasution; Audrina Ernes (PRIMER (Prima Medical Journal), 2023)
Backgrounds: Gliomas are one of the most common primary brain tumours. Gliomas may present with imaging that can mimic other primary brain lesions. Objective: To demonstrate the role of radiological imaging (CT scan and MRI) in determining the diagnosis as well as a reference for determining subsequent therapy in patients with primary brain lesions. Case: This case report describes a 67-year-old male patient with complaints of decreased consciousness and seizures. The patient had a history of headache since 2 months ago and was not accompanied by limb weakness. Discussion: The appearance of low-grade glioma on CT scan gives an image resembling infarction where both give an appearance of hypodense lesions on non-contrast CT and do not enhance on CT with contrast. Therefore, further imaging such as MRI imaging is required. Conclusion: MRI is important modality in assisting the diagnosis of patients with primary brain lesions and can assist in selecting the appropriate treatment.